Competency 8 in reading comprehension and the ECE test in rural educational institutions of the department of Tacna - Flores Sánchez, María Elvira (2023)
This study focused on analyzing the possible pedagogical causes of the differences in the results obtained by second-year students from two rural educational institutions in Tacna in the Census Student Assessment (ECE) and the assessment of COMPETENCY 8 (Reads various types of written texts in the mother tongue) conducted in 2019. A mixed methodological strategy was employed, involving documentary review techniques (to obtain statistical data) and interviews (to gather testimonies from teachers in the Communication area) —made in 2020— to delve into the perceptions and experiences of students regarding classroom assessment processes and the ECE development processes. The analysis of the data led to the conclusion that the reasons for the differences in results are primarily due to pedagogical factors on the one hand, and emotional factors on the other, specifically the stress and fatigue experienced by students when facing an assessment like the ECE.